Numerical modeling for drilling fluid invasion into hydrate-bearing sediments and effects of permeability - Huang, Tianjia; Zhang, Yu; Li, Gang; Li, Xiaosen; Chen, Zhaoyang (Journal of Natural Gas Science and Engineering, 2020)
Drilling fluid invasion into hydrate-bearing sediments could induce hydrate dissociation and complicate heat and mass transfer around wellbore, and further affect mechanical strength of hydrate-bearing sediments and accurateness of wellbore logging interpretations. In this study, a cylindrical numerical model was established to study the characteristics of drilling fluid invasion into hydrate-bearing sediments and the effects of permeability on this process. The distributions of temperature, pressure, saturation, and salinity of pore water around wellbore at different time were obtained. The pressure and temperature around wellbore gradually increase, and the hydrate around wellbore dissociates with the high-temperature drilling fluid invasion. Meantime, water and gas generated from hydrate dissociation gradually migrate outward and then form 'secondary hydrate' in some areas outside wellbore. Dissociation and formation of hydrate can sharply change the salinity of pore water around wellbore. The drilling fluid invasion and hydrate dissociation ranges become larger when the intrinsic permeability is higher. The salinity in sediments decreases sharply while the dilution range is narrow when drilling fluid invasion into hydrate-bearing sediments with low permeability. In addition, the permeability decline exponent of the Masuda model has a significant influence on drilling fluid invasion. However, the Corey exponents of the relative permeability model only have a limited influence on drilling fluid invasion into hydrate-bearing sediments with low intrinsic permeability (e.g., 5.5 mD), while they have a noticeable influence on hydrate-bearing sediments with high intrinsic permeability (e.g., 75 mD).